1994
DOI: 10.1364/ao.33.004719
|View full text |Cite
|
Sign up to set email alerts
|

Blue shadows: physical, physiological, and psychological causes

Abstract: The apparent blueness of outdoor shadows has two main causes: the illumination of the shadows by blue skylight and the enhancement of the perception of blue by simultaneous color contrast. Other physiological mechanisms, such as brightness contrast and afterimages, can also affect the perception of a shadow's blueness. Preferential scattering by the cornea does not seem to make a major contribution. Despite these effects, color constancy causes most people to observe an empirically blue shadow as colorless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…Informal reports from observers showed that the bluish tints present in steel or silver appear largely unnoticed, yet transform to strong shades of bronze or gold when the color content is inverted. This perceptual asymmetry also accounts for the finding that yellowish sepia tones appear more colorful than an equivalent bluish tint, while blue shades such as shadows appear less colorful [4]. Moreover, even when blues are exaggerated, we observed they tend (unlike yellowish tints) to be perceived as a property of the lighting rather than the surfaces.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Informal reports from observers showed that the bluish tints present in steel or silver appear largely unnoticed, yet transform to strong shades of bronze or gold when the color content is inverted. This perceptual asymmetry also accounts for the finding that yellowish sepia tones appear more colorful than an equivalent bluish tint, while blue shades such as shadows appear less colorful [4]. Moreover, even when blues are exaggerated, we observed they tend (unlike yellowish tints) to be perceived as a property of the lighting rather than the surfaces.…”
supporting
confidence: 61%
“…We found that surfaces are much more likely to be perceived as white or gray when their color is varied along bluish directions, compared to equivalent variations along yellowish (or reddish or greenish) directions. This selective bias may reflect a tendency to attribute bluish tints to the illuminant rather than the object, consistent with an inference that indirect lighting from the sky and in shadows tends to be bluish [4]. The blue-yellow asymmetry has striking effects on the appearance of images when their colors are reversed, turning white to yellow and silver to gold, and helps account for the different colors experienced in “the dress” that recently consumed the internet.…”
supporting
confidence: 55%
“…For instance, shadows are known to be slightly bluer (e.g., Churma, 1994;Fine, MacLeod, & Boynton, 2003); that is, shadow borders are usually accompanied by some chromatic contrast. A series of luminance X-junctions with a constant luminance ratio can be produced by a reflectance pattern (as in Figure 1).…”
mentioning
confidence: 99%
“…The visible spectrum of sunlight is almost evenly spread between 440 to 700 nm (Figure 1A) [12]. In contrast, the visible spectrum of shadows is shifted towards shorter wavelengths (Figure 1B) [12].…”
Section: Letter To the Editormentioning
confidence: 99%